How to Design a Study and Write a Grant in Radiology? - Pankaj Gupta; Manphool Singhal (Indian Journal of Radiology and Imaging)
Radiology as a specialty has grown immensely over the last few decades. The advancements in diagnostic radiology are facilitated by state-of-the-art equipment and a revolution in computation. Parallelly, interventional radiology has benefited and interventional radiologists are at the forefront of several therapeutic procedures. One of the key factors in the growth of radiology is high-quality research. Although the formulation of research questions and hypotheses is similar, the research methodology in diagnostic radiology differs from other specialties. High-quality research requires funds. Thus, it is essential for academic radiologists pursuing research in radiology to be able to write successful grants and secure funds. In this review article, we discuss the strategies to design a study and write successful grants.